Pengaruh Keterlibatan Kerja dan Gaya Komunikasi Terhadap Prestasi Kerja dengan Komitmen Organisasi Sebagai Variabel Intervening pada Pegawai SMPN 1 Dharmasraya - Decky Chandra; Mondra Neldi; Ramdani Bayu Putra; Hasmaynelis Fitri (Yayasan Kawanad, 2022)
This study aims to determine how much influence work involvement and communication style have on work performance with organizational commitment as an intervening variable on employees of SMPN 1 Dharmasraya. The method used is Structure Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. By distributing questionnaires as many as 63 respondents. The results of data analysis concluded that there was a significant positive effect between work involvement variables on organizational commitment variables. There is a positive and insignificant effect between the communication style variables on the organizational commitment variable. There is a significant positive effect between work involvement variables on work performance variables. There is a positive and insignificant effect between the communication style variables on the work performance variables. There is a significant positive effect between organizational commitment variables and work performance variables. There is a positive and insignificant effect between work involvement variables on work performance through organizational commitment. There is a positive and insignificant effect between the variables of communication style on work performance through organizational commitment.